Commodity Price Returns and Energy Sector Stock Returns: Evidence from Indonesia - Wiwin Eni Sulistiandari; Henny Wirianata (Golden Ratio of Finance Management, 2026)
Global commodity price fluctuations have become an important factor influencing the performance of the energy sector in capital markets. This study aims to examine the effects of world oil price returns, world gold price returns, and world coal price returns on energy sector stock returns on the Indonesia Stock Exchange (IDX) during the 2021–2025 period. The study employs secondary daily data from 27 main board energy sector companies listed on the IDX, selected using a purposive sampling method. The data were analyzed using Ordinary Least Squares (OLS), while Vector Autoregression (VAR) and the Granger Causality Test were employed as complementary analytical methods. The results indicate that world oil price returns and world coal price returns have positive and significant effects on energy sector stock returns, whereas world gold price returns do not have a significant effect. These findings suggest that global energy commodities, particularly oil and coal, play a more influential role than gold in explaining energy sector stock returns in Indonesia. The study provides practical implications for investors by highlighting the importance of monitoring global commodity price movements in investment decision-making. In addition, it contributes empirical evidence to the growing literature on the relationship between commodity price returns and energy sector stock returns in emerging markets.